2007
DOI: 10.1128/aac.00749-06
|View full text |Cite
|
Sign up to set email alerts
|

Development of a New Methodology for Screening of Human Immunodeficiency Virus Type 1 Microbicides Based on Real-Time PCR Quantification

Abstract: Potential topical retrovirucides or vaginal microbicides against human immunodeficiency virus type 1 (HIV-1) include nonnucleoside reverse transcriptase inhibitors (NNRTIs). To be successful, such agents have to be highly active against cell-free virions. In the present study, we developed a new real-time PCR-based assay to measure the natural endogenous reverse transcription (NERT) activity directly on intact HIV-1 particles in the presence of reverse transcriptase (RT) inhibitors. We further evaluated the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Efavirenz (1.25 μM) was also able to inhibit endogenous RT activity at the same levels described in previous publications (Figure 1B, white bars). The concentrations applied for NERT assay are expected to be higher since it has been demonstrated that cell-free virions are less permeable to drugs when compared to cell-associated virions [29]. All together, these results show that emetine blocks HIV intravirion RT activity and suggest that this compound could potentially be used as an HIV RT inhibitor.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Efavirenz (1.25 μM) was also able to inhibit endogenous RT activity at the same levels described in previous publications (Figure 1B, white bars). The concentrations applied for NERT assay are expected to be higher since it has been demonstrated that cell-free virions are less permeable to drugs when compared to cell-associated virions [29]. All together, these results show that emetine blocks HIV intravirion RT activity and suggest that this compound could potentially be used as an HIV RT inhibitor.…”
Section: Resultsmentioning
confidence: 96%
“…We also explored if emetine could block HIV-1 RT activity directly in cell-free virus particles. To address this question, we used the Natural Endogenous Reverse Transcriptase (NERT) assay based on qPCR [29]. The pre-exposure of virus particles to dNTPs stimulate NERT activity (Figure 1B, dNTPs + black bar).…”
Section: Resultsmentioning
confidence: 99%
“…Primers and probe were designed to a conserved region within the HIV‐1 LTR: sense SSF1 (5′‐GCT AAC TAG GGA ACC CAC TGC TT‐3′), anti‐sense SSR1 (5′‐CAA CAG ACG GGC ACA CAC TAC T‐3′), probe SS (5′FAM‐AGC CTC AAT AAA GCT TGC CTT GAG TGC TTC‐BHQ1‐3′) (Aguiar et al. ). Briefly, 5 μ L of RNA was added into 12.5 μ L amplification mix containing 2.5 μ M of each primer, 5 μ M of probe and RNAse‐free water to a 25 μ L final volume.…”
Section: Methodsmentioning
confidence: 99%
“…Real-time quantitative RT-PCR cDNAs were amplified using the TaqMan â Universal Master Mix amplification kit (Roche Molecular System, Branchburg, NJ, USA). Primers and probe were designed to a conserved region within the HIV-1 LTR: sense SSF1 (5 0 -GCT AAC TAG GGA ACC CAC TGC TT-3 0 ), anti-sense SSR1 (5 0 -CAA CAG ACG GGC ACA CAC TAC T-3 0 ), probe SS (5 0 FAM-AGC CTC AAT AAA GCT TGC CTT GAG TGC TTC-BHQ1-3 0 ) ( Aguiar et al 2007). Briefly, 5 lL of RNA was added into 12.5 lL amplification mix containing 2.5 lM of each primer, 5 lM of probe and RNAse-free water to a 25 lL final volume.…”
Section: Nucleic Acid Extraction and Cdna Synthesismentioning
confidence: 99%
“…The drug was generally antivirally active at concentrations that were several orders of magnitude lower than its toxicity value. Dapivirine, as also reported for UC-781, is able to penetrate the envelope of HIV-1 particles, likely (partially) due to its high lipophilicity, resulting in inactivation of the virus before target cell infection (Costa et al 2005 ;Aguiar et al 2007 ;Njai et al 2005 ).…”
Section: The Diarylpyrimidine Derivative Dapivirinementioning
confidence: 85%